2006
DOI: 10.1016/j.ydbio.2005.11.002
|View full text |Cite
|
Sign up to set email alerts
|

KATP channels in mouse spermatogenic cells and sperm, and their role in capacitation

Abstract: Mammalian sperm must undergo a series of physiological changes after leaving the testis to become competent for fertilization. These changes, collectively known as capacitation, occur in the female reproductive tract where the sperm plasma membrane is modified in terms of its components and ionic permeability. Among other events, mouse sperm capacitation leads to an increase in the intracellular Ca(2+) and pH as well as to a hyperpolarization of the membrane potential. It is well known that ion channels play a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
76
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(84 citation statements)
references
References 66 publications
6
76
0
Order By: Relevance
“…This structure has been detected in spermatozoa from several mammals and in sea urchin (210), and it is now proposed that it functions as a Ca 2ϩ store. In support of this proposal, inositol trisphosphate (IP 3 ) receptors (IP 3 Rs) have been detected in the RNE (261). The second structure found in mammalian sperm is the cytoplasmic droplet ( see FIG.…”
Section: Mammalian Spermatogenesismentioning
confidence: 71%
See 2 more Smart Citations
“…This structure has been detected in spermatozoa from several mammals and in sea urchin (210), and it is now proposed that it functions as a Ca 2ϩ store. In support of this proposal, inositol trisphosphate (IP 3 ) receptors (IP 3 Rs) have been detected in the RNE (261). The second structure found in mammalian sperm is the cytoplasmic droplet ( see FIG.…”
Section: Mammalian Spermatogenesismentioning
confidence: 71%
“…IP 3 Rs and RyRs are the major intracellular Ca 2ϩ channels located primarily in ER-type intracellular stores. In addition, two-pore channels (TPCs) were recently described as intracellular Ca 2ϩ channels located in acidic organelles such as lysosomes (199,585,586).…”
Section: E Intracellular Ca 2؉ Channelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies from our group have demonstrated that inwardly rectifying K ϩ channels contribute to this hyperpolarization (5,6). In addition, we documented that an electrogenic Na ϩ /HCO 3 Ϫ cotransporter hyperpolarizes mouse sperm when external HCO 3 Ϫ is elevated (7).…”
mentioning
confidence: 61%
“…There are at least three different sources of ATP generation in the spermatozoa [RodriguezMiranda et al 2008], including oxidative phosphorylation in the sperm mitochondria [Halangk et al 1985], glycolysis in the fibrous sheath of the sperm tail principal piece [Krisfalusi et al 2006], and the conversion of ADP to ATP by adenylate kinase [Schoff et al 1989;Foresta et al 1992]. Of particular interest to the present study is the detection of adenylate kinase-dependent KATP-potassium channels in the sperm acrosome [Acevedo et al 2006].…”
Section: Discussionmentioning
confidence: 99%